2012
DOI: 10.1212/wnl.0b013e3182648b8b
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial for geotropic horizontal canal benign paroxysmal positional vertigo

Abstract: This study provides Class I evidence that barbecue rotation and Gufoni maneuvers are effective in the treatment of geotropic HC-BPPV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
86
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(90 citation statements)
references
References 28 publications
3
86
0
1
Order By: Relevance
“…Yetiser et al [2] , Kim et al [7] , Lee et al [8] and Akkuzu et al [10] detected lower interpeak amplitudes on the affected sides of BPPV patients. In these studies, the VEMP asymmetry ratios of healthy controls were used as normalized data and compared with those of the BPPV group.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Yetiser et al [2] , Kim et al [7] , Lee et al [8] and Akkuzu et al [10] detected lower interpeak amplitudes on the affected sides of BPPV patients. In these studies, the VEMP asymmetry ratios of healthy controls were used as normalized data and compared with those of the BPPV group.…”
Section: Discussionmentioning
confidence: 95%
“…There has also been no standard approach for the evaluation of VEMP asymmetry. Yetiser et al [2] defined asymmetry over 25% as VEMP asymmetry, although in other studies, data obtained from the control group were regarded as normative data, and VEMP asymmetry was defined as a value above an upper limit calculated by the formula [upper limit=mean of the control group+(2×standary deviation)] [ 7,8,10] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim JS et al 9 held a comparative study between the Gufoni maneuver and BBQ (270°) maneuver in 170 consecutive patients with geotropic HC-BPPV. They demonstrated that booth were effective treatment methods [38 of 55 (69.1%) for BBQ rotation, and 39 of 64 (60.9%) for the Gufoni maneuver], even when applied only twice in the initial visit day.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to its higher success rate, the Gufoni maneuver 15 is not only less time consuming 12 but also easier to perform than the BBQ 360° maneuver in obese or elderly persons and in patients with cervical pain and stiffness 9,17 . It is worth mentioning that one third of our patients were over 70 years old.…”
Section: Resultsmentioning
confidence: 99%